(untitled) (Carte Romanze, 2021)
The essay examines from a diachronic perspective the formulae of incantation addressed to Mother Earth, of which there are at least three examples dated between the 9th and 10th centuries, two composed in scripta latina rustica and one in the Occitan language (the most famous “blessings of Clermont-Ferrand”). The three enchantments are aimed at curing diseases of various kinds and in their respective final charm, according to a principle of magical thought, they order the evil to move from the inside to the outside of the body, finally begging Mother Earth to welcome it. The earliest antecedent of this formula is identified in Varrone’s De re rustica, where the poem was part of a healing ceremony.